The protein identification resource (PIR). - George, D G (1986)
The Protein Identification Resource, which provides the scientific community with an efficient on-line computer system designed for the identification and analysis of protein sequences and their corresponding coding sequences, has been established. The resource consists of an integrated computer system composed of a number of protein and nucleic acid sequence databases and the software necessary to analyze this information effectively.